KEMAMPUAN RASIO KEUANGAN SEBAGAI INDIKATOR DALAM MEMPREDIKSI FINANCIAL DISTRESS PERUSAHAAN - Hirawati, Heni; P, Panji Kusuma; V, Dian Marlina (JAB (Jurnal Akuntansi & Bisnis), 2019)
ABSTRACTThis research aims to examine the ability of financial ratios as indicators in predicting company’s financial distress. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2012-2017. The sampling technique in this research is using purposive sampling technique in which companies are divided into two categories: companies that do not experience financial distress and companies that are categorized as experiencing financial distress. Financial ratios as indicators in predicting financial distress used in this study consist of current ratio, total liabilities to total assets, current liabilities to total assets, return on total assets, net income to sales, sales growth and sales to total assets. The research method used is logistic regression analysis methods. The results of this study indicate that return on assets and sales to total assets can be used in predicting financial distress.Keyword: financial distress, financial ratio